Perbandingan Strategi dan Pola Pengembangan Pesantren dan Diniyyah Berwawasan Multikultural - Miftahul Huda; Rhoni Rodin (Journal of Islamic Education Research, 2021)
The purpose of this study are: (1) to determine the educational system, strategies, and various patterns of pesantren development with a multicultural perspective; (2) to determine the education system, strategies, and various patterns of diniyyah development with a multicultural perspective; (3) to compare systems, strategies and patterns of education in pesantren and diniyyah with multicultural insight. In this study using a qualitative approach. The method used is a research library. The data analysis technique used is content analysis. The result of this research is that multicultural education at the pesantren is reflected in the content of the curriculum that teaches students insights on the diversity of beliefs such as teaching special material muq?ranat al-ady?n. Secondary formal diniyyah education consists of formal ulya diniyyah education and ma'had Aly. Strategies and development patterns in Diniyyah that have a multicultural perspective through a curriculum, namely extracurricular and intracurricular subjects and activities.